2017
DOI: 10.1021/acs.jctc.7b00495
|View full text |Cite
|
Sign up to set email alerts
|

Fully Atomistic Aβ40 and Aβ42 Oligomers in Water: Observation of Porelike Conformations

Abstract: Oligomers formed by amyloid β-protein (Aβ) are central to Alzheimer's disease (AD) pathology, yet their structure remains elusive. Of the two predominant Aβ alloforms, Aβ40 and Aβ42, the latter is more strongly associated with AD. Here, we structurally characterized Aβ40 and Aβ42 monomers through pentamers which were converted from previously derived coarse-grained (DMD4B-HYDRA) simulations into all-atom conformations and subjected to explicit-solvent MD. Free energy landscapes revealed that structural differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 89 publications
7
30
1
Order By: Relevance
“…The β-barrel structure as a model for small Aβ40/Aβ42 oligomers was also supported by recent hydrogen exchange mass spectrometry 24 and NMR studies 25 . Aβ40/Aβ42 oligomers with pore-like conformations was also observed in a recent computational study combining coarse-grained and all-atom simulations 26 . These β-barrel oligomers capable of spanning across the lipid bilayer and thus compatible to the “amyloid-pore” hypothesis of amyloid toxicity 15 17 have been postulated as the early aggregation intermediates exerting toxic effects on cells 11 .…”
Section: Introductionsupporting
confidence: 68%
“…The β-barrel structure as a model for small Aβ40/Aβ42 oligomers was also supported by recent hydrogen exchange mass spectrometry 24 and NMR studies 25 . Aβ40/Aβ42 oligomers with pore-like conformations was also observed in a recent computational study combining coarse-grained and all-atom simulations 26 . These β-barrel oligomers capable of spanning across the lipid bilayer and thus compatible to the “amyloid-pore” hypothesis of amyloid toxicity 15 17 have been postulated as the early aggregation intermediates exerting toxic effects on cells 11 .…”
Section: Introductionsupporting
confidence: 68%
“…In both simulations, Aβ(1–42) trimers are compact and much less structured than mature fibrils. Consistent with Voelker et al, 48 they form pores with a radius of 1.7–2.1 Å, suggesting molecules like water and Ca 2+ ions can pass through them. In simulation 1 , where the simulation began with random configurations, for the first time, we obtained trimer structures containing small β-barrels, but no barrels were found in simulation 2 .…”
Section: Introductionsupporting
confidence: 87%
“…In the latter study, pores with a radius in the range of 1.5–2.5 Å were detected in the Aβ42 trimer, but no β-barrel structure was found. The reason that β-barrels were found in our simulation but not in ref ( 48 ) is probably related to various modeling protocols. In this work, we used the all-atom model and performed REMD simulation with 72 replicas of 600 ns each.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…AβP(1-40), as 5-8-mer oligomers, forms pore-like structures in the membranes, as revealed by 3-D computer simulations [119]. Nuclear magnetic resonance (NMR) studies show that AβP(1-42) pores are composed of tetrameric and hexameric oligomers [120]. Voelker et al demonstrated that AβP(1-40) as well as AβP(1-42) formed trimers to pentamers that could form ion channels in water [121].…”
Section: Aβp-induced Ca Dyshomeostasismentioning
confidence: 99%